An Enhancement of the Filipino proofing tool - Cayabyab, Arlene G. and Talliedo, Maria Katrina P. 4 0 16; 5 (2005)
u
Undergraduate Thesis: (BSCS major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2